Activity and safety of cinchonine nanostructured lipid carriers as a hair growth stimulant in mice model of androgenetic alopecia - Hariyanti, Hariyanti; Mauludin, Rachmat; Sumirtapura, Yeyet Cahyati; Kurniati, Neng Fisheri (Penerbit Universiti Kebangsaan Malaysia, 2023)
Androgenetic alopecia (AA) is a hair growth disorder characterized by hair loss and miniaturization of the size of follicles and dermal papillae. Cinchonine is a quinoline alkaloid that can increase VEGF production and potential as a hair growth stimulant. This study aimed to determine the morphology, penetration (in vitro), as well as safety and activity of cinchonine nanostructured lipid carriers (CN-NLC) serum as a hair growth stimulant. Preparation of CN-NLC serum using a combination of micro-emulsification and ultra-sonification methods, characterization of CN-NLC serum included morphology and closed hair follicle diffusion methods. Dermal and eye irritation test using New Zealand rabbit strain with primary irritation index parameters. Hair growth stimulant activity test using Swiss Webster mice strain, induced with the hormone testosterone. Observations were performed at 7, 14, and 21 days with hair length and histology parameters. CN-NLC serum morphology is a spherical shape with size ±500 nm, diffusion of serum CN-NLC (open hair follicles) of 23.92±0.84%; (close hair follicles) of 11.37±2.29%; and CN solution of 6.00±0.72%. CN-NLC serum are non-irritant with a primary irritation index of 0.0. Activity tests showed hair length on days 7; 14 and 21 were increased by 20.24-23.74%; 33.47-36.43%, and 39.30-39.97% (P≤0.05). Histological data showed an increase in the number and size of both dermal papillae and hair follicles compared to the control group. CN-NLC serum can improve the penetration of CN into hair follicles. CN-NLC serum is safe and effective as a hair growth stimulant in the treatment of AA.